Peran Humas dalam Menangani Krisis Citra Sistem OSS di Kementerian Investasi Indonesia - Sarah Tazkiyatun Nufus Adha; Muhammad Al Assad Rohimakumullah (Kaganga:Jurnal Pendidikan Sejarah dan Riset Sosial Humaniora, 2022)
The purpose of the study was to determine the role of public relations in dealing with the OSS system image crisis that received negative comments on sosial media, especially Instagram @bkpm_id. The method used is qualitative with an observative approach, this study uses data collection methods in the form of interviews and observations. The results of this study are descriptive narratives that explain what BKPM's PR has done in dealing with the OSS image crisis. The results obtained are that BKPM's PR does not use a special strategy to improve the OSS image, but is more inclined towards sosial media monitoring by responding to user complaints. The conclusion of the research shows that public relations uses the public relations method in dealing with the OSS system image crisis at the Indonesian Ministry of Investment. Keywords: Image, Ministry of Investment, OSS